2019
DOI: 10.3389/fcimb.2019.00078
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of Brucella spp. and Elimination of Carryover Using Multiple Cross Displacement Amplification Coupled With Nanoparticles-Based Lateral Flow Biosensor

Abstract: Brucella spp .is capable of causing disease in a range of animal hosts, and human brucellosis is regarded as a life-threating disease. A novel isothermal amplification technique, termed multiple cross displacement amplification (MCDA), was employed for detecting all Brucella species strains. Brucella- MCDA targets the Bscp31 gene ( Brucella species-specific gene) to specifically design a set of 10 primers. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 23 publications
0
34
0
Order By: Relevance
“…The newly developed E. faecalis- MCDA-LFB method was capable of assaying 10 fg of E. faecalis genomic DNA (Figure 4), which was more sensitive than E. faecalis- LAMP-LFB detection (250 fg per reaction) reported by the previous study 25. Although the amplification products could be detected equally with the MG method used in the present study, the LFB was deemed as the preferred method as observing the amplification results is more objective and does not need any apparatus 19,27. In conclusion, the newly E. faecalis -MCDA-LFB assay in this study is a valuable method for the convenient, rapid, sensitive, specific, visual, reliable, and low-cost detection of E. faecalis in clinical and environmental samples, especially in resource-constrained settings.…”
Section: Discussionmentioning
confidence: 50%
“…The newly developed E. faecalis- MCDA-LFB method was capable of assaying 10 fg of E. faecalis genomic DNA (Figure 4), which was more sensitive than E. faecalis- LAMP-LFB detection (250 fg per reaction) reported by the previous study 25. Although the amplification products could be detected equally with the MG method used in the present study, the LFB was deemed as the preferred method as observing the amplification results is more objective and does not need any apparatus 19,27. In conclusion, the newly E. faecalis -MCDA-LFB assay in this study is a valuable method for the convenient, rapid, sensitive, specific, visual, reliable, and low-cost detection of E. faecalis in clinical and environmental samples, especially in resource-constrained settings.…”
Section: Discussionmentioning
confidence: 50%
“…Comparing the above three assay methods, we deemed the LFB was more visual. And it did no needs special instruments and regents [16,17]. Besides, LFB can detect both the IS6110 and mpb64 genes and make them visualized in a single test at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…strains and Shigella spp [13], Vibrio parahaemolyticus [14] and Listeria monocytogenes [15]. Our team also created the MCDA method for Brucella spp [16] and Neisseria meningitidis [17] detection successfully.…”
mentioning
confidence: 99%
“…To overcome the drawbacks of such traditional detections, the multiple cross displacement amplification (MCDA) technique is a novel, low-cost, sensitive, and rapid isothermal amplification technology similar to LAMP, but with more specificity and sensitivity in microorganism assay, 13 which has been applied to detect several pathogens such as Mycobacterium tuberculosis, Neisseria meningitides, and Listeria monocytogenes. [14][15][16] Previous studies suggested that MCDA amplification products could been analyzed by various technologies, including agarose gel, turbidimetry, and colorimetric indicators (malachite green reagent).…”
Section: Introductionmentioning
confidence: 99%